The Theory of Islamization of Knowledge: A Comprehensive Review of Historical Progress, Objectives, and Implementation Process (Jagannath University Journal of Arts, 2026)
The Islamization of Knowledge (IoK) is an intellectual endeavor incorporating Islamic precepts into contemporary academic fields. The study examines the reconciliation of secular knowledge systems with Islamic epistemology, resulting in philosophical and ethical issues for Muslim civilizations. The main aim is to explore the historical evolution, goals, methodology, and implementation procedures of IoK. The study employs a qualitative analysis of significant writings and historical progressions to pinpoint essential figures such as Ismail Raji al-Faruqi, Syed Muhammad Naqib al-Attas, and Abdul Hamid A. Sulayman. Their frameworks prioritize the integration of Islamic ideals with modern disciplines via both theoretical and practical methodologies. Research indicates that IoK aims to reconcile knowledge with Islamic principles by bridging the discrepancies between revelation and reason. The findings emphasize IoK's capacity to transform education and intellectual frameworks while also revealing obstacles such as opposition from secular institutions and the necessity for transdisciplinary knowledge. The study's implications suggest that enhancing IoK approaches can bolster Islamic research, promoting a balanced integration of faith and reason within contemporary academia.Jagannath University Journal of Arts, v-5, i-01, 2025: p160-175